PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MS GLOW DI PACITAN - Clarissa Paulina Audry; Yunita Fitri Wahyuningtyas (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2023)
This study aims to determine whether there is an influence of brand image and product quality on purchasing decisions of MS Glow in Pacitan. This study will look at the effect of brand image and product quality partially and simultaneously on purchasing decisions. The data collection technique used was a questionnaire, interviews and observations conducted from September 2022 to January 2023. The sampling technique used was purposive sampling, data analysis using descriptive analysis, multiple linear regression analysis, coefficient of determination, F test, and t test. By testing the hypothesis, it is known that brand image and product quality simultaneously have a positive and significant effect on consumer purchasing decisions of MS Glow in Pacitan. Partially the product quality variable has a positive and significant influence on purchasing decisions, while the brand image variable has no effect on purchasing decisions.